SURVEI PERILAKU PENGGUNAAN SMARTPHONE DAN MANFAATNYA DI KALANGAN PELAJAR SEKOLAH MENENGAH ATAS - Pardede, Sanggam; Siagian, Lasma; Sinaga, Dearlina; Simanjuntak, Meliana (Dharmas Education Journal (DE_Journal), 2024)
This study aims to describe smartphone usage behaviors among high school students in Tarutung City, and students' perceptions of the benefits of smartphones for learning. It is a quantitative study with a descriptive survey design. The research population consists of 3,604 students, and the sample size was determined using the Krejcie table, with 354 students selected at a 95% confidence level and a 5% margin of error. Stratified random sampling was used to select the sample. The results show that smartphones serve a dual role, functioning as a highly valuable learning aid and an alternative source of knowledge. However, smartphones also present challenges to students' social and psychological development, potentially fostering negative behaviors, such as decreased social interactions, weakened emotional connections, and increased risk of cyberbullying. Students perceive smartphones as having a positive potential to support learning. A limitation of this research is that it only included high school students, limiting its generalizability across all student smartphone users. Future research is recommended to include samples from all levels of education.